2001
DOI: 10.1007/s004320100293
|View full text |Cite
|
Sign up to set email alerts
|

Expression of angiogenic factors and tumor progression in human neuroblastoma

Abstract: Purpose: The growth and metastasis of malignant tumors is largely dependent on angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Clinical studies correlating the levels of VEGF-C in neoplasms and their metastatic potential showed controversial results (Andre et al, 2000;Cao et al, 1998;Clarijs et al, 2001b;de Waal et al, 1997;Eggert et al, 2000;George et al, 2001;Gunningham et al, 2000;Gunningham et al, 2001;Hamada et al, 2000;Jones et al, 2000;Karkkainen et al, 2002;Kinoshita et al, 2001;Komuro et al, 2001;Niki et al, 2000;Oh et al, 1997;Ohta et al, 1999;Pepper, 2001;Salven et al, 1998;Ueda et al, 2001;Yonemura et al, 2001). However, a significant correlation between VEGF-C and lymph node metastasis has been observed in thyroid (Bunone et al, 1999;Fellmer et al, 1999), head and neck (O-charoenrat et al, 2001), breast (Kurebayashi et al, 1999), esophageal (Kitadai et al, 2001), prostate (Tsurusaki et al, 1999), gastric (Ichikura et al, 2001;Yonemura et al, 1999), lung (Kajita et al, 2001;Niki et al, 2000;Ohta et al, 2000), cervical (Hashimoto et al, 2001), renal (Tang et al, 2001), endometrial (Hirai et al, 2001), and colorectal (Akagi et al, 2000) neoplasms.…”
Section: Microvessel Density As a Prognostic Factor For Human Neoplasmsmentioning
confidence: 99%
“…Clinical studies correlating the levels of VEGF-C in neoplasms and their metastatic potential showed controversial results (Andre et al, 2000;Cao et al, 1998;Clarijs et al, 2001b;de Waal et al, 1997;Eggert et al, 2000;George et al, 2001;Gunningham et al, 2000;Gunningham et al, 2001;Hamada et al, 2000;Jones et al, 2000;Karkkainen et al, 2002;Kinoshita et al, 2001;Komuro et al, 2001;Niki et al, 2000;Oh et al, 1997;Ohta et al, 1999;Pepper, 2001;Salven et al, 1998;Ueda et al, 2001;Yonemura et al, 2001). However, a significant correlation between VEGF-C and lymph node metastasis has been observed in thyroid (Bunone et al, 1999;Fellmer et al, 1999), head and neck (O-charoenrat et al, 2001), breast (Kurebayashi et al, 1999), esophageal (Kitadai et al, 2001), prostate (Tsurusaki et al, 1999), gastric (Ichikura et al, 2001;Yonemura et al, 1999), lung (Kajita et al, 2001;Niki et al, 2000;Ohta et al, 2000), cervical (Hashimoto et al, 2001), renal (Tang et al, 2001), endometrial (Hirai et al, 2001), and colorectal (Akagi et al, 2000) neoplasms.…”
Section: Microvessel Density As a Prognostic Factor For Human Neoplasmsmentioning
confidence: 99%
“…18 Expression of VEGF and VEGFR correlates with a higher stage of NB. 19,20 Furthermore, VEGF may act as a growth factor for NB cells independent of its pro-angiogenic action. 21 Bevacizumab, a humanized monoclonal antibody 22 binding all five isoforms of human VEGF, has been extensively studied in adults with cancer and has US Food and Drug Administration (FDA) approval for the therapy of several cancers usually in combination with chemotherapy.…”
mentioning
confidence: 99%
“…range[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; nine had objective responses with modest reductions in MIBG score (median -1; range -1 to -4). BM and soft tissue responses were documented in five (27%) and one (10%) patients, respectively.Responses did not correlate with disease status at study entry: objective responses were noted in five of 10 patients with primary chemorefractory disease versus seven of 23 patients who had progressed or relapsed (P = 0.28 by 2 test) prior to BIT.…”
mentioning
confidence: 99%
“…The clinicopathological significance of VEGF-D expression in patients with NBs studied at mRNA level is inconsistent. There was no association between expression levels and clinical stages in some studies, 9,11 although VEGF-D expression was increased in MYCNamplified compared with non-MYCN amplified Stage 4 NBs. 9 Our findings may have clinical implications because it has been shown that inhibition of VEGF-A results in a paradoxical increase in VEGF-D in gliobastomas in rats, indicating that VEGF-D is an alternative mediator of angiogenesis, in line with its role in inducing angiogenesis through receptor VEGFR-2.…”
Section: Discussionmentioning
confidence: 94%
“…8 Previous studies of VEGF-C, VEGF-D and VEGFR-3 have reported their expression at mRNA level in NB cell lines and clinical samples. [9][10][11][12] Histological studies of VEGF-C 13 or VEG-FR-3 protein 14 have been conducted using a small number of NB samples 13,14 or NB samples modified by chemotherapy. 13 We performed a detailed protein expression analysis of VEGF-C, VEGF-D and VEGFR-3 in a series of neuroblastic tumours to determine their potential significance based on their associations with clinicopathological and biological features and the value of expression as predictors of outcome.…”
Section: Introductionmentioning
confidence: 99%